1983
DOI: 10.1002/ajmg.1320150410
|View full text |Cite
|
Sign up to set email alerts
|

Possible introduction of Huntington's chorea into Pacific islands by New England whalemen

Abstract: Huntington's disease (HD) has been reported in two isolated South Pacific islands, New Britain in Papua New Guinea, and Malaita in the Solomon Islands. The earliest presumptive choreics in these foci were born in the latter part of the 19th century, prior to the colonial period. It is known that these islands were visited by certain New England whalers in the precolonial era, and inspection of the crew lists of these whalers shows many men with surnames common to families in New England known to have produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1994
1994

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The interesting and plausible suggestion has been made that the gene could have been introduced by the crews of visiting whaling ships from North America, which were active in the sperm-whale fishery in the first half of the nineteenth century. Scrimgeour (1983) searched the records of whaling voyages and found that a number of crew members had surnames present in known HD families from New England, recorded in the Davenport und Muncey archives, preserved at the University of Minnesota. While no direct link has been proven, the predominance of New Englanders in the whaling industry and the frequent sexual relations with islanders make this a reasonable hypothesis for these small populations, where genetic drift could have subsequently increased the gene frequency in some cases.…”
Section: New Populations Of European Originmentioning
confidence: 99%
“…The interesting and plausible suggestion has been made that the gene could have been introduced by the crews of visiting whaling ships from North America, which were active in the sperm-whale fishery in the first half of the nineteenth century. Scrimgeour (1983) searched the records of whaling voyages and found that a number of crew members had surnames present in known HD families from New England, recorded in the Davenport und Muncey archives, preserved at the University of Minnesota. While no direct link has been proven, the predominance of New Englanders in the whaling industry and the frequent sexual relations with islanders make this a reasonable hypothesis for these small populations, where genetic drift could have subsequently increased the gene frequency in some cases.…”
Section: New Populations Of European Originmentioning
confidence: 99%